Phenotyping Cardiopulmonary Exercise Limitations in Chronic Obstructive Pulmonary Disease - Gelinas, Jinelle; Harper, Megan; Sasso, John; Wright, Stephen; Melzer, Bernie; Agar, Gloria; Guenette, Jordan; duManoir, Gregory; Roman, Michael; Rolf, J. Douglass; Eves, Neil (Frontiers in Physiology, 2022)
Background: Exercise limitation in chronic obstructive pulmonary disease (COPD) is commonly attributed to abnormal ventilatory mechanics and/or skeletal muscle function, while cardiovascular contributions remain relatively understudied. To date, the integrative exercise responses associated with different cardiopulmonary exercise limitation phenotypes in COPD have not been explored but may provide novel therapeutic utility. This study determined the ventilatory, cardiovascular, and metabolic responses to incremental exercise in patients with COPD with different exercise limitation phenotypes. Methods: Patients with COPD (n=95, FEV1:23-113%pred) performed a pulmonary function test and incremental cardiopulmonary exercise test. Exercise limitation phenotypes were classified as: ventilatory (peak ventilation [VEpeak]/maximal ventilatory capacity [MVC]≥85% or MVC-VEpeak≤11L/min, and peak heart rate [HRpeak]<90%pred), cardiovascular (VEpeak/MVC<85% or MVC-VEpeak>11L/min, and HRpeak≥90%pred) or combined (VEpeak/MVC≥85% or MVC-VEpeak≤11L/min, and HRpeak≥90%pred). Results: FEV1 varied within phenotype: ventilatory (23-75%pred), combined (28-90%pred), and cardiovascular (68-113%pred). The cardiovascular phenotype had less static hyperinflation, a lower end-expiratory lung volume and larger tidal volume at peak exercise compared to both other phenotypes (p<0.01 for all). The cardiovascular phenotype reached a higher VEpeak (60.8±11.5L/min vs. 45.3±15.5L/min, p=0.002), cardiopulmonary fitness (VO2peak: 20.6±4.0ml/kg/min vs. 15.2±3.3ml/kg/min, p<0.001) and maximum workload (103±34W vs. 72±27W, p<0.01) versus the ventilatory phenotype, but was similar to the combined phenotype. Conclusion: Distinct exercise limitation phenotypes were identified in COPD that were not solely dependent upon airflow limitation severity. ~50% of patients reached maximal heart rate, indicating that peak cardiac output and convective O2 delivery contributed to exercise limitation. Categorizing patients with COPD phenotypically may aid in optimizing exercise prescription for rehabilitative purposes.